Impact of CBR Value of Soil in Soaked and Unsoaked Conditions Based on 2018 Division 3 Bill Specifications - Lubis, Muhammad Yusuf Parlagutan (PT Inovasi Pratama Internasional, 2024)
Soil is a construction material that is used as embankment to provide better soil bearing capacity and resilience to the soil itself. This research aims to determine the comparison of the CBR value of soil in soaked and unsoaked conditions based on the provisions of the 2018 Directoral of Highways Specifications Division 3.2 regarding embankments. In the research, the CBR results in the soaked condition were 6.15% and the unsoaked CBR was 9.64%. The CBR value requirement based on the 2018 Specifications is a minimum of 6% of the results obtained that meet the requirements for embankment CBR value, where the CBR value in the soaked condition is greater than the unsoaked condition. Based on these results, soaked embankment soil is suitable for use if the soil is compacted under conditions of continuous work, while unsoaked embankment soil can be used after the CBR value meets after the soaking process or a drying period of 4 days (96 hours).